A Hypervirulent Isolate Identified from a Race 1 Ralstonia solanacearum Strain from Tomato (Lycopersicon esculentum Mill. cv. L-180) - Orlina-Villareal, M. E. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2008)
Results of inoculation of 10 Ralstonia solanacearum strains to resistant (Hawaii 7996, C108, 508), moderately resistant (Improved Pope, L-180-1) and susceptible (Yellow Plum, L390) tomato cultivars revealed four of the strains to be the most virulent based on their wilting percentages. The four strains were then compared by reisolation from the inoculated plants, DNA extraction and repetitive extragenic palindromic - polymerase chain reaction (REP-PCR) fingerprinting. Out of the 542 fingerprinted DNA samples from reisolations, two of the strains, one of which was T523, had isolates which manifested variable REP fingerprints. An isolate, T523-731, had a missing 0.4 kb band and additional bands of about 0.7 kb and 0.45 kb. Reinoculation of T523-731 on the same set of tomato cultivars resulted in an average wilting of 96% on two resistant cultivars (C108 and 508) and 17% on the highly resistant cultivar Hawaii 7996. In contrast, reinoculation of an isolate (T523-726) that exhibited the fingerprint of the parent strain, resulted in 16.7% wilting in cv. 508 but did not cause wilting in cvs. C-108 and Hawaii 7996. The parent strain T523 caused 3% wilting in cv. 508, and similarly did not cause wilting in cvs. C- 108 and Hawaii 7996. Similar results were obtained with a subsequent virulence test. The isolate T523-731 was considered a hypervirulent isolate as it was able to overcome the resistance of the tomato cultivars that were earlier found to be highly resistant to bacterial wilt.